PENGARUH SIMEBANK PADA MATERI TEKS PROSEDUR KONTEKSTUAL TERHADAP LITERASI KEUANGAN SISWA KELAS IV SD - Barid Nafsiyah, Elwira; Tur Rosidah, Cholifah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The research is motivated by students who lack or are unable to properly and correctly understand the use of money, leading them to occasionally spend their pocket money wastefully and struggle to control themselves from spending it consumptively. The goal of this research is to determine the effect of bank saving simulations in contextual procedural text material on the financial literacy of fourth-grade elementary school students. This research uses a pre-experimental method with a Quasi-Experimental design, specifically a Posttest Only Control Design. The population in this study consists of Class IV A and IV C, with a total of 54 students. Data collection in this research was conducted using tests. Statistical analysis was performed using methods aligned with the research title, namely